2016
DOI: 10.1007/s12195-016-0464-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methacrylate-Based Thermoresponsive Polymer Brush Composition on Fibroblast Adhesion and Morphology

Abstract: Thermoresponsive polymers are being used increasingly in cell culture applications due to their temperature dependent surface properties. Poly(MEO2MA-co-OEGMA) (PMO) brushes offer tunable physical properties via variation in the copolymer ratio, but the effects of composition on cell-substrate interactions is unclear. To this end, a series of PMO brushes (0â8% OEGMA) was fabricated and L-929 fibroblast adhesion and morphology was quantified in the presence of serum (FBS) or after functionalization via the adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The ( x:y ) ratio can be tuned during polymer synthesis to manipulate the LCST, which, in turn, impacts hydrophobicity and other physico‐chemical properties that impact interactions with biological systems. For example, studies with poly(MeO 2 MA x ‐ co ‐OEGMA y ) based cell culture substrates comprised of 0–8% OEGMA have shown that cell adhesion and spreading are enhanced on more hydrophobic surfaces with increased ( x:y ) ratio . Here, we utilize similar copolymer ratios (5–10% OEGMA) to elicit distinct AgNP surface hydrophobicity at a physiological temperature of 37°C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ( x:y ) ratio can be tuned during polymer synthesis to manipulate the LCST, which, in turn, impacts hydrophobicity and other physico‐chemical properties that impact interactions with biological systems. For example, studies with poly(MeO 2 MA x ‐ co ‐OEGMA y ) based cell culture substrates comprised of 0–8% OEGMA have shown that cell adhesion and spreading are enhanced on more hydrophobic surfaces with increased ( x:y ) ratio . Here, we utilize similar copolymer ratios (5–10% OEGMA) to elicit distinct AgNP surface hydrophobicity at a physiological temperature of 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of serum proteins, it is well established that NP are rapidly coated with a protein corona, and the molecular identity and function of adsorbed proteins are important mediators of cellular interactions . For poly(MeO 2 MA x ‐ co ‐OEGMA y ) immobilized on polyelectrolyte substrates, the adsorption capacity for model proteins, albumin and fibronectin, is correlated to the ratio of the hydrophobic MeO 2 MA unit in the copolymer composition . Thus, it is likely that the differential cytotoxicity observed in response to Ag‐poly(MeO 2 MA x ‐ co ‐OEGMA y ) is, in part, attributed to differences in the extent of protein corona formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations